Implementasi Model Pembelajaran Problem Based Learning untuk Meningkatkan Hasil Belajar PJOK Materi Penyakit Menular Covid 19 - Rinto Primaraga Ibrahim; Made Satyawan; Gede Suwiwa (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan Undiksha, 2022)
The purpose of this research is to improve learning outcomes of PJOK on Covid-19 infectious disease material in class VII A of SMPN 1 Rogojampi through the implementation of the problem-based learning model. This type of CAR research (Classroom Action Research) with the teacher as a researcher, is carried out in two cycles consisting of planning, action, observation and reflection stages. The research subjects were students of class VII A of SMPN 1 Rogojampi totaling 33 students, consisting of 15 male students and 18 female students. Methods of data collection is done by using observation and test methods. Observation is used to determine the activeness of students in participating in learning and the test or assessment method used to retrieve data on PJOK learning outcomes after the implementation of learning problem base learning in the form of scores (scores). The results of the implementation of cycles I and II, data analysis and processing as well as indicators of success that have been carried out, show that the average student learning outcomes classically there is an increase in this classroom action research, namely 71.8 in the first cycle and 80.9 in the second cycle. Meanwhile, classical student learning completeness who scored above 75 reached 72.7% in the first cycle and 84.8% in the second cycle. In conclusion, the average student learning outcomes classically and classical student learning completeness increased after the implementation of the problem base learning model was applied to class VII A SMPN 1 Rogojampi students.